Effect of magnesium and vitamin B6 supplementation on mental health and quality of life in stressed healthy adults: Post‐hoc analysis of a randomised controlled trial. (6th May 2021) - Noah, Lionel; Dye, Louise; Bois De Fer, Béatrice; Mazur, André; Pickering, Gisèle; Pouteau, Etienne
Abstract: Magnesium status and vitamin B6 intake have been linked to mental health and/or quality of life (QoL). In an 8‐week Phase IV randomised controlled study in individuals with low magnesemia and severe/extremely severe stress but who were otherwise healthy, greater stress reduction was achieved with magnesium combined with vitamin B6 than with magnesium alone. We present a previously unreported secondary analysis of the effect of magnesium, with and without vitamin B6, on depression, anxiety, and QoL. Adults with Depression Anxiety Stress Scales (DASS‐42) stress subscale score >18 were randomised 1:1 to magnesium + vitamin B6 combination (Magne B6 ® ; daily dose 300 and 30 mg, respectively) or magnesium alone (Magnespasmyl ® ; daily dose 300 mg). Outcomes included changes from baseline in DASS‐42 depression and anxiety scores, and QoL (Short Form‐36 Health Survey). DASS‐42 anxiety and depression scores significantly improved from baseline to week 8 with both treatments, particularly during the first 4 weeks. Improvement in QoL continued over 8 weeks. Participants' perceived capacity for physical activity in daily life showed greater improvement with magnesium + vitamin B6 than magnesium alone (Week 4). In conclusion, magnesium supplementation, with or without vitamin B6, could provide a meaningful clinical benefit in daily life for individuals with stress and low magnesemia.